Biodistribution and pharmacokinetics of 188Re-liposomes and their comparative therapeutic efficacy with 5-fluorouracil in C26 colonic peritoneal carcinomatosis mice - Tsai CC (Dove Medical Press, 2011)
Chia-Che Tsai1, Chih-Hsien Chang1, Liang-Cheng Chen1, Ya-Jen Chang1, Keng-Li Lan2, Yu-Hsien Wu1, Chin-Wei Hsu1, I-Hsiang Liu1, Chung-Li Ho1, Wan-Chi Lee1, Hsiao-Chiang Ni1, Tsui-Jung Chang1, Gann Ting3, Te-Wei Lee11Institute of Nuclear Energy Research, Taoyuan, 2Cancer Center, Taipei Veterans General Hospital, Taipei, 3National Health Research Institutes, Taipei, Taiwan, ROCBackground: Nanoliposomes are designed as carriers capable of packaging drugs through passive targeting tumor sites by enhanced permeability and retention (EPR) effects. In the present study the biodistribution, pharmacokinetics, micro single-photon emission computed tomography (micro-SPECT/CT) image, dosimetry, and therapeutic efficacy of 188Re-labeled nanoliposomes (188Re-liposomes) in a C26 colonic peritoneal carcinomatosis mouse model were evaluated.Methods: Colon carcinoma peritoneal metastatic BALB/c mice were intravenously administered 188Re-liposomes. Biodistribution and micro-SPECT/CT imaging were performed to determine the drug profile and targeting efficiency of 188Re-liposomes. Pharmacokinetics study was described by a noncompartmental model. The OLINDA|EXM® computer program was used for the dosimetry evaluation. For therapeutic efficacy, the survival, tumor, and ascites inhibition of mice after treatment with 188Re-liposomes and 5-fluorouracil (5-FU), respectively, were evaluated and compared.Results: In biodistribution, the highest uptake of 188Re-liposomes in tumor tissues (7.91% ± 2.02% of the injected dose per gram of tissue [%ID/g]) and a high tumor to muscle ratio (25.8 ± 6.1) were observed at 24 hours after intravenous administration. The pharmacokinetics of 188Re-liposomes showed high circulation time and high bioavailability (mean residence time [MRT] = 19.2 hours, area under the curve [AUC] = 820.4%ID/g*h). Micro-SPECT/CT imaging of 188Re-liposomes showed a high uptake and targeting in ascites, liver, spleen, and tumor. The results were correlated with images from autoradiography and biodistribution data. Dosimetry study revealed that the 188Re-liposomes did not cause high absorbed doses in normal tissue but did in small tumors. Radiotherapeutics with 188Re-liposomes provided better survival time (increased by 34.6% of life span; P < 0.05), tumor and ascites inhibition (decreased by 63.4% and 83.3% at 7 days after treatment; P < 0.05) in mice compared with chemotherapeutics of 5-fluorouracil (5-FU).Conclusion: The use of 188Re-liposomes for passively targeted tumor therapy had greater therapeutic effect than the currently clinically applied chemotherapeutics drug 5-FU in a colonic peritoneal carcinomatosis mouse model. This result suggests that 188Re-liposomes have potential benefit and are safe in treating peritoneal carcinomatasis of colon cancer.Keywords: biodistribution, dosimetry, 5-fluorouracil, micro-SPECT/CT, 188Re-liposomes